RETRACTED: The Effect of Work Motivation, Teamwork and Physical Work Environment on the Performance of PT Faradi Pesona Indonesia Employees - Dheazalfa Sukmarini; Ahmad Cik; Kumba Digdowiseiso (Journal of Social Science)
This research is the result of research on the Effect of Work Motivation, Teamwork, and Physical Work Environment on Employee Performance at PT Faradi Pesona Indonesia. The research method used is quantitative method. The results of this study used primary data in the form of a questionnaire to 60 respondents, the results of the study stated that there was a positive and significant influence between the variables Work Motivation, Teamwork and Physical Work Environment on Employee Performance at PT Faradi Pesona Indonesia. Therefore the results of the study have been able to influence work motivation, teamwork and physical work environment on the performance of employees of PT Faradi Pesona Indonesia.